KOMUNIKASI VERBAL DAN NONVERBAL - Tri Indah Kusumawati (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2016)
Verbal communication is communication by using vebal symbols. Language verbal symbol is an impressive of human achieveness. There are rules for every language that are phonology, syntax, semanctc and pragmatic. Otherwise, nonverbal communication is a communication process that message is sent not using words. The example of nonverbal communication is body movement, body language, face expression, and eye contact, the using of clothes, hair cut, etc, symbols, and also the way of speaking such as, intonation, stress, voice quality, emotional style, and speaking style.Keywords: Komunikasi, Verbal, Nonverbal.